Reconfiguring Habits and Behaviors in Urban Centers: A Qualitative Study on the Impact of Perceptions on Public Insecurity - Martínez-Martínez, Oscar A. (Victims & offenders, 2022)
After more than ten years of the United States (U.S.)-Mexico’s War on Drugs, Mexico continues to experience a crisis of public insecurity. This crisis has contributed to several Mexican cities being described as some of the most dangerous in the world. Drawing on qualitative research methods, this study investigates the effect of increasing perceptions of public insecurity on individuals’ habits and behaviors in 46 municipalities in the states of Mexico City, Estado de Mexico, Tamaulipas, and Oaxaca. Data is collected through in-depth interviews in urban areas (N = 184). The results provide public policy insights that could address the crisis of insecurity. An assertion is made that to reform the communities investigated, social violence must be tackled, and we attempt to provide a blueprint for such an initiative in this study.